Catherine Pfeifer (CPWF) explains the importance of Spatial Analysis and Modelling - Pfeifer, Catherine (CGIAR Challenge Program on Water and Food, 2011)
During the International Forum on Water and Food, South Africa, 14-17 November 2011, Catherine Pfeifer explains the importance of using Spatial Analysis and Modelling with the research work of the CGIAR Challenge Program on Water and Food